Exploring the diversity and antimicrobial potential of actinomycetes isolated from different environments in Saudi Arabia: a systematic review - Helmi, Noof Refat (Frontiers in Microbiology, 2025)
The increasing prevalence of antimicrobial resistance (AMR) presents a significant global health challenge, underscoring the urgent need for novel antimicrobial agents. Actinomycetes, particularly Streptomyces species, are well known for synthesizing bioactive compounds with antibacterial, antifungal, and antiviral properties. This review explores the diversity and antimicrobial potential of actinomycetes from Saudi Arabia’s unique ecosystems, including terrestrial (soil, rhizosphere), aquatic (marine, freshwater), extreme (deserts, caves, hot springs, mountains, and mangroves), and other unique environments. The adaptation of these microorganisms to harsh environmental conditions has driven the evolution of unique strains with enhanced biosynthetic capacities. Several studies have demonstrated their antimicrobial efficacy against multidrug-resistant pathogens, including methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae, Pseudomonas aeruginosa, and Candida albicans. However, challenges in actinomycete research persist, including difficulties in culturing rare strains, limited genomic characterization, and high production costs. Recent advancements, such as genome mining, metagenomics, AI-driven bioinformatics, and CRISPR-based gene activation, offer promising avenues for unlocking novel antimicrobial compounds. Additionally, synthetic biology, advanced fermentation technologies, and nanotechnology-based drug delivery systems are enhancing the industrial scalability of actinomycete-derived antibiotics. Beyond antimicrobials, actinomycete-derived compounds show potential applications in oncology, immunotherapy, and agriculture. Alternative therapeutic strategies, including quorum sensing inhibitors, phage therapy, and combination therapies, are being explored to combat AMR. Cutting-edge analytical techniques, such as mass spectrometry, liquid chromatography, and nuclear magnetic resonance spectroscopy (NMR), are essential for structural elucidation and mechanism characterization of new bioactive compounds. To harness Saudi Arabia’s microbial biodiversity effectively, interdisciplinary collaborations between microbiologists, biotechnologists, and pharmaceutical industries are crucial. Sustainable bioprospecting and advanced bioprocessing strategies will facilitate the translation of actinomycete-derived bioactive compounds into clinically viable therapeutics. Expanding research efforts into underexplored Saudi ecosystems can lead to groundbreaking discoveries in antibiotic development and beyond.